Deny Sanctioned Officials Access to Government: The Best Strategy for Minimizing Public Corruption Until Appropriate Legislation is Enacted by the Liberian Government - Gobewole, Stephen (Advances in Social Sciences Research Journal, 2024)
This study examines corrupt behaviors in the Liberian government due to the inability of Liberia’s anti-corruption commission and its judicial system inability to hold public officials accountable. Moreover, since the nation’s inception government officials have used bribery, rent-seeking, and public resources embezzlement to accumulate personal wealth. This study analyzes survey, empirical, and sanctions data collected by Transparency International, The United States Department of the Treasury, United States Foreign Assistance by Country from The United States government, The United Nations Development Programme, and drawing on Liberia’s Political Economy by S. Gobewole, 2016. It then correlates associations between the numbers measuring government corruption, sanctioned official behaviors, and incidence of foreign assistance to Liberia to demonstrate an increase in public corruption due to officials’ behavior. This has resulted from Liberia’s judicial institutions incapacity to regulate bribery, rent seeking, and resource embezzlement, which have perpetuated and increased public corruption in the Liberian government, a situation that demands legislative action to punish United States Department of the Treasury sanctioned public officials.